2017
DOI: 10.1007/s10900-017-0419-3
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Factors Related to Conventional and Traditional Tobacco Use Among California Asian Indian Immigrants

Abstract: California's tobacco control program contracted for tobacco use surveillance of Asian Indian Americans to address the paucity of information about tobacco use in this community, given their growing proportion of California's population. This study examined correlates of conventional (CTU) and Asian Indian traditional tobacco use (TTU) in a population-based sample of predominantly immigrant Asian Indian adults residing in California (N = 3228). The analytic sample (n = 2140) was limited to self-identified immig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 41 publications
2
17
0
2
Order By: Relevance
“…Past research has found males to have higher prevalence or odds of SLT use when compared to women (18,19,27), and our study was no exception. In our study, a longer percentage of time lived in the US was significantly associated with ever use of SLT among females, and speaking English very well was significantly associated with ever and current use of SLT among males.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Past research has found males to have higher prevalence or odds of SLT use when compared to women (18,19,27), and our study was no exception. In our study, a longer percentage of time lived in the US was significantly associated with ever use of SLT among females, and speaking English very well was significantly associated with ever and current use of SLT among males.…”
Section: Discussionsupporting
confidence: 61%
“…South Asians are the second largest Asian group in the United States (US), and are one of the fastest growing racial/ethnic groups (15). While the prevalence of SLT among South Asians in the US is largely unknown and potentially underestimated, often because traditional health surveillance measures for tobacco do not capture traditional Asian products (16), the current published prevalence rates remain high (16)(17)(18)(19). However, a limited number of studies have focused on SLT use among the large South Asian communities in New York City (20)(21)(22), despite some suggestion of its high prevalence (16).…”
Section: Introductionmentioning
confidence: 99%
“…The main result of the present investigation is the significantly lower risk of being a current smoker and for drinking alcohol in highly religious individuals in comparison with less religious or non-religious people. This result is consistent with findings from previous studies with immigrant samples ([ 23 , 24 , 25 , 26 , 27 , 28 ] and with the results of the Polish General Social Survey ( n = 1526) [ 49 ] and the Survey of Health, Ageing, and Retirement in Europe ( n = 16,557) ([ 50 ]. Several possible explanations can be provided for the protective role of religiosity against substance consumption.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the studies on this topic have been conducted in the USA in Latino and Asian Indian immigrants. In sum, the scarce literature on the association between religiosity and health-related behaviors in immigrants has consistently shown an inverse relationship between religiosity and tobacco [ 23 , 24 , 25 ] as well as alcohol consumption or alcohol use disorders ([ 25 , 26 , 27 , 28 ]; a positive association between religiosity and physical activity (however, only one study has examined this topic [ 25 ]); and mixed results concerning religiosity and being overweight/obese—one survey reported no significant relationship [ 25 ] and one [ 29 ] demonstrated a positive association (found only for Asian Indians practicing Hinduism or Sikhism, but not for Muslims).…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, a study with 2140 participants in California noted that Indian immigrants had lower past-30-day use of conventional tobacco products (4.2%) compared to the general California adult population (14.6%). Conversely, Indian immigrants had higher ever use of traditional tobacco products (64.9%) and a majority (96.6%) had already used these products prior to immigrating to the U.S. [19].…”
Section: Introductionmentioning
confidence: 98%